Prevalence and factors associated with stress among mothers of children with cerebral palsy in an NGO in Satkhira, Bangladesh - Debnath, Sankar Chandra (2021)
Cerebral palsy is a chronic neurological disorder for children. The incidence of cerebral palsy is high in developing countries. Women who are primary caregivers of children with cerebral palsy have more responsibility for a long time caring. Mothers of children with cerebral palsy can develop stress while caring for their children. This study aims to determine the prevalence of maternal stress and its associated factors among mothers of children with cerebral palsy in an NGO in Satkhira, Bangladesh. A cross-sectional study was done using a simple random sampling method and guided questionnaires. A pre-test was performed to check the reliability and validity of each instrument. Statistical Package for Social Sciences (SPSS) version 25 was used for data analysis. A Chi-square test was done to determine the association between independent and dependent variables. Multiple Logistic Regression analysis was performed to determine the factors that predict maternal stress. The significance level was set as a p-value of less than 0.05. The prevalence of maternal stress was 59.3% among mothers of children with cerebral palsy. Sociodemographic characteristics of mothers, the majority respondents were aged between 18-28 years (41%), with primary education (48.8%), married mothers (84.3%), housewife (74.4%), mothers living in an extended family (59.3%), and average family income (44.8%). The sociodemographic characteristics of children were the younger age group (60.5%), with male children (62.2%). The majority of respondents had good knowledge (57.8%), lower negative family impact (58.1%), and higher formal social support (54.4%). There was a significant association between maternal stress and age of mothers (p<0.001), education of mothers (p<0.001), types of the family (p=0.05), family income (p<0.001), child’s age (p<0.001), child’s gender (p=0.05), and number of children (p<0.001). Regarding maternal appraisal and social support, there was a significant association between maternal stress and negative family impact (p<0.001) and informal social support (p<0.001). The fitted final model of regression reported the independent predictors of maternal stress followed by mothers’ aged 29-38 (AOR=3.844, 95%CI=1.831-8.069), divorced/separated (AOR=56.196, 95%CI=8.764-360.340), core family (AOR=2.879, 95%CI=1.538-5.388), child’s age 1-7 (AOR=2.294, 95%CI= 0.992-5.300), male children (AOR=2.108,95%CI=1.142-3.88), higher negative family impact (AOR=3.206, 95%CI=1.171-8.772), lower informal social support (AOR=2.340, 95CI%=1.309-4.185) respectively. This study found that mothers of children with cerebral palsy perceived higher stress levels with child age, male child, negative family impact, and informal social support. The factors identified in this study could help to develop policies and strategies to minimize maternal stress among mothers of children with cerebral palsy in Bangladesh.